Effect of 18F-DCFPyL PET on changes in management of patients with prostate cancer: a systematic review and meta-analysis - Wang, Hui; Zhu, HongMei; Li, GuanNan; Dai, JiaoNa; Huang, HeXiao; Jia, Qiong (Frontiers in Medicine, 2024)
Purpose Prostate-specific membrane antigen (PSMA)-targeted imaging has gained increasing interest in its application in prostate cancer lesion detection. Compared with 68Galium (68Ga), 18Fluoride (18F)-labeled imaging agent has easier syntheses, lower price, and a longer half-time. 2-(3-{1-Carboxy-5-[(6-[18F]fluoro-pyridine-3-carbonyl)-amino]-pentyl}-ureido)-pentanedioic acid positron emission tomography (18F-DCFPyL PET) has been recently approved by the U.S. Food and Drug Administration. Several studies have proven its superiority to conventional imaging techniques in detecting prostate cancer lesions. However, the impact of 18F-DCFPyL PET on the management of patients with prostate cancer is not well established. Thus, we performed a systematic review and meta-analysis of available data to evaluate the impact of 18F-DCFPyL PET on the management of patients with prostate cancer. Methods The PubMed, Embase, Scopus, and Cochrane databases were searched up to April 2024. Studies that reported the proportion of changes in management after 18F-DCFPyL PET was performed in patients with prostate cancer were included. The Grading of Recommendations Assessment, Development, and Evaluation system was used for the quality evaluation of the included studies. The proportion of changes in management was pooled using a random effects model. Meta-regression analyses were performed to assess the potential correlation between the PET positivity and management changes. Results Fourteen studies (3,078 patients with prostate cancer) were included in our review and analysis. The pooled percentage of management changes was 43.5% (95% confidence interval [CI]: 33–54%). In patients with biochemical recurrent and for primary staging, the pooled percentage was 50% (95% CI: 39–60%) and 22% (95% CI: 15–29%), respectively. In the meta-regression analyses, PET positivity was detected as a significant predictor of management change (p = 0.0023). Conclusion 18F-DCFPyL PET significantly affects the management of patients with prostate cancer. Higher PET positivity rate significantly correlated with a higher proportion of management changes in patients with prostate cancer. However, more studies are still needed to confirm the important role of 18F-DCFPyL PET in the management of prostate cancer. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/#myprospero, CRD42022339178.